The longitudinal relationships of problematic social media use, self-transcendence values and school adaptation: a two-wave study - Ting Li; Jiaqiong Xie; Yanjie Shan; Ke Chen (BMC Psychology)
Abstract This study aims to explore the temporal dynamics of the relationships between problematic social media use(PSMU), self-transcendence values, and school adaptation among college students. Methods This study employed longitudinal cross-lagged analysis and structural equation modeling to investigate whether there is a mutual influence among PSMU, self-transcendence values, and school adaptation. Additionally, the study explored whether these variables serve as intermediaries in the associations between the other two variables. Results Two thousand six hundred sixty-eight students were longitudinally followed up for two-wave.The results indicated PSMU predicted self-transcendence values and school adaptation 6 months later; self-transcendence values predicted PSMU and school adaptation 6 months later; and school adaptation predicted self-transcendence values and PSMU 6 months later. Moreover, each of them plays a mediating role in the association between the other two variables. Conclusions These results support and expand the Self-worth Theory and Self-determination Theory that there is a bidirectional relationship between PSMU, self-transcendence values, and school adaptation. This result has implications for helping college students adapt to college life and reduce PSMU.